Nomogram for predicting pathological complete response to neoadjuvant chemoimmunotherapy in patients with resectable non-small cell lung cancer - Liu, Wenyi; Sui, Zhilin; Wang, Chunguang; Deng, Youjun; Cai, Songhua; Jia, Ran; Yu, Zhentao; Kang, Mingqiang; Zhang, Baihua (Frontiers in Cell and Developmental Biology, 2025)
ObjectivesNeoadjuvant chemoimmunotherapy is increasingly employed in resectable non-small cell lung cancer (NSCLC), with variable pathological complete response (pCR) rates. Currently, no reliable preoperative tool is available for predicting pCR. This study develops a nomogram based on clinical variables to predict pCR and guide individualized surgical decisions.MethodsWe retrospectively analyzed data from 179 NSCLC patients (stages IIB-IIIB) who received neoadjuvant chemoimmunotherapy followed by resection (2019–2022). Variables included demographics, smoking history, comorbidities, treatment details, and pathology. Univariate and multivariate logistic regression identified pCR predictors, which were incorporated to build a nomogram. Performance was assessed via area under the curve (AUC), calibration, and decision curve analysis (DCA).ResultsOf 179 patients, 92 (51.4%) achieved pCR. Multivariate analysis identified independent predictors: non-squamous histology (OR 0.344 (non-squamous vs. squamous), 95% CI 0.151–0.707, p = 0.006), positive family history (OR 10.76 (positive vs. negative), 95% CI 1.903–203.3, p = 0.027), shorter smoking cessation duration (defined as time in days from last cigarette to treatment start) (OR 0.999 (per day), 95% CI 0.999–0.999, p = 0.033), older age (OR 1.053 (per year), 95% CI 1.005–1.106, p = 0.032), and more treatment cycles (OR 1.621 (per cycle), 95% CI 1.007–2.661, p = 0.049). The nomogram showed modest discrimination (AUC 0.709, 95% CI 0.633–0.785), good calibration, and net benefit on DCA, though it has not been externally validated and is limited by single-center data, small sample size, high pCR rate, and skewed demographics (95.5% male, 92.7% smokers), potentially limiting generalizability to diverse populations such as females or non-smokers.ConclusionThis nomogram, derived from routine clinical data, predicts pCR after neoadjuvant chemoimmunotherapy in NSCLC, offering a tool for thoracic surgeons to optimize treatment and surgical planning, despite its modest discriminative power, by serving as a complementary aid in resource-limited settings where biomarkers may not be readily available. External validation in larger, multi-center cohorts is essential.